The nuclear envelope protein Net39 is essential for muscle nuclear integrity and chromatin organization - Andres Ramirez-Martinez (Nature Portfolio, 2021)
The nuclear envelope tethers chromatin to the nuclear periphery to control genome architecture. Here, the authors show that Net39 preserves the integrity and gene expression of muscle nuclei in mice, and it may contribute to the pathogenesis of Emery–Dreifuss muscular dystrophy.